A new species of Chrysozephyrus associated with Lithocarpus corneus (Lepidoptera: Lycaenidae: Theclini) - Hsu, Yu-Feng (Zootaxa, 2018)
Chrysozephyrus laoshanensis, sp. nov., is described and illustrated from Cenwanglaoshan in the western part of Guangxi Province, China and Ha Giang Province of Vietnam. The new species is associated with Lithocarpus corneus, which has not previously been recognized as a hostplant for Theclini or any lepidopterous specialist feeder. The valva and brachia of the new species are distinct from all known members of Chrysozephyrus.